تسيير الميزانية العامة في المؤسسة العمومية - بوكروش, حليمة (My University, 2023)
The study aimed to identify the procedures used to manage the general budget of the public institution for neighborhood health, starting with how it is prepared and ending with the disbursement of its revenues. The study reached several conclusions, the most important of which is that the general budget represents a major tool used to achieve local development goals, as well as the effective role played by the financial controller to ensure optimal utilization of public funds.
دراسة حالة المؤسسة العمومية للصحة الجوارية - "سيدي لخضر
Keywords: general budget, expenditures, revenues, financial control, public institution